Strangers in Hostile Lands: Exposure to Refugees and Right-Wing Support in Germany's Eastern Regions - Max Schaub; Johanna Gereke; Delia Baldassarri (Comparative Political Studies, 2021)
Does local exposure to refugees increase right-wing support? This paper studies a case uniquely suited to address this question: the allocation of refugees to the rural hinterlands of eastern Germany during the European refugee crisis. Similar to non-urban regions elsewhere, the area has had minimal previous exposure to foreigners, but distinctively leans towards the political right. Our data comprise electoral outcomes, and individual-level survey and behavioral measures. A policy allocating refugees following strict administrative rules and a matching procedure allow for causal identification. Our measurements confirm the presence of widespread anti-immigrant sentiments. However, these are unaffected by the presence of refugees in respondents' hometowns: on average, we record null effects for all outcomes, which we interpret as supporting a sociotropic perspective on immigration attitudes. Masked by these overall null findings, we observe convergence: local exposure to refugees appears to have pulled both right- and left-leaning individuals more towards the center.
doi:10.7910/DVN/C6NONY
Keywords: 330; right-wing support; refugees; Germany; immigration